Murder Likes It Hot : Downward Dog Mystery #6 - Weber, Tracy, 1964- (Woodbury, Minnesota : Midnight Ink, 2019)
When an employee is found dead at the local homeless shelter for youth, yoga instructor Kate Davidson sets aside her fertility and financial woes to support and defend the teenagers.
Keywords: Mystery fiction